THE IMPACT OF TEACHING AND LEARNING METHODS DURING COVID-19 ON THE MASTERY LEVEL OF TECHNICAL SKILLS OF TECHNICAL AND VOCATIONAL EDUCATION STUDENTS - Nuraisyah Alia Hanaf; Hanifah Jambari; Nurul Aini Mohd Ahyan; Mohamad Rasidi Pairan; Nur Hazirah Noh @ Seth (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The COVID-19 pandemic profoundly impacted educational systems worldwide, including Technical and Vocational Education and Training (TVET). The shift from traditional classroom-based learning to online or hybrid models presented unique challenges, especially for fields that heavily rely on hands-on, practical experience to develop technical skills. Online learning became a big challenge for TVET students. This is because TVET students require more practical experience in addition to theoretical knowledge. As a result of movement and other physical constraints, technical skills could not be honed during the Covid-19 period. Thus, this study was conducted to identify the mastery level of technical skills of TVET students when the Covid-19 broke out. In addition, this study was also conducted to identify suitable teaching and learning methods that can be used during the pandemic period for mastering technical skills. A random sampling method was used and a total of 86 respondents were recruited from TVET students in year 4. This study is quantitative method, and the research instrument used is a questionnaire survey form. The data obtained were analysed using the Statistical Package Social Sciences (SPSS) software version 26.0. The findings of the study showed that the students’ mastery of technical skills was at a moderate level; and the use of teaching and learning methods during the Covid-19 period was also at a moderate level. The researcher expects that this study will help in providing information to certain parties in order to increase the mastery level of technical skills as well as improving the teaching and learning styles, should unexpected situations occur again.